The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11883-014-0442-0
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions for Cardiovascular Disease Risk Reduction: A Systematic Review of the Effects of Diet Composition, Food Provision, and Treatment Modality on Weight Loss

Abstract: The purpose of this systematic review was to evaluate, synthesize, and interpret findings from recent randomized controlled trials (RCTs) of dietary and lifestyle weight loss interventions examining the effects of 1) diet composition, 2) use of food provision, and 3) modality of treatment delivery on weight loss. Trials comparing different dietary approaches indicated that reducing carbohydrate intake promoted greater initial weight loss than other approaches but did not appear to significantly improve long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
(143 reference statements)
0
21
0
1
Order By: Relevance
“…Moreover, treatment can be delivered over many modalities (in-person, phonebased, and internet). 68 Clinical trials testing the effects of comprehensive behavioral programs have found weight losses averaging $10.7 kg (11% of body weight) over 30 weeks. 66,69 Nonetheless, even with comprehensive behavioral treatment, gradual weight regain is often observed overtime, resulting in modest ($5%) overall weight losses at 3 to 4 years.…”
Section: Effective Lifestyle Interventions For Weight Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, treatment can be delivered over many modalities (in-person, phonebased, and internet). 68 Clinical trials testing the effects of comprehensive behavioral programs have found weight losses averaging $10.7 kg (11% of body weight) over 30 weeks. 66,69 Nonetheless, even with comprehensive behavioral treatment, gradual weight regain is often observed overtime, resulting in modest ($5%) overall weight losses at 3 to 4 years.…”
Section: Effective Lifestyle Interventions For Weight Controlmentioning
confidence: 99%
“…Postpartum women face several challenges to attending traditional face-to-face weight loss interventions; this may explain the high attrition rates (30-40%) seen in many postpartum weight loss programs. [135][136][137][138] Delivering weight loss intervention via telephone and/or other modalities (i.e., internet and mobile technology) may offer an alternative to face-to-face interventions 68 and may be particularly useful for postpartum women. 139 Regardless of modality, sufficient "dose" of treatment and incorporation of evidence-based weight control strategies are likely more important in determining postpartum intervention efficacy.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded, however, that longer, pragmatic, interdisciplinary, open-source interventions are needed. In a similar way, meta-analyses performed by Neve et al [ 22 ], Manzoni et al [ 23 ], Kodama et al [ 24 ], and Dutton et al [ 25 ] found that Internet use in obesity treatment programmes has a modest but significant effect on weight control. These reviews also point out variations between trials (with smaller effect sizes, and inconsistent findings across studies), mixed results, heterogeneity of designs, and low generalization of the findings, however, and they emphasise that better descriptions of components of effective interventions are still needed.…”
Section: Introductionmentioning
confidence: 70%
“…Overall 20/28 of the studies demonstrated cost-effectiveness of an intervention, but we cannot rule out publication bias skewing our results towards including studies demonstrating cost-effectiveness. However, the share of studies reporting (cost) effectiveness is similar to comparable reviews in the field [ 56 ].…”
Section: Discussionmentioning
confidence: 99%